A phytochemical investigation of the leaves of Piper nigrum L. - Maramara, Emmanuel G. (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
The constituents of the leaves of Piper nigrum L. (Fam. Piperaceae) were separated and isolated using extractive and chromatographical techniques. Specific chemical tests demonstrated the presence of groups of compounds commonly found in leaves. The presence of alkaloids is shown by chemical testing. Thin layer chromatography separated components satisfactorily. Rf values of separated components were consistently reproduced.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, October 1978.
Keywords: Piper nigrum; Black Pepper; Paminta